PERBANDINGAN KADAR UREUM PASIEN GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISA DI RS X TAHUN 2022 - PQNAW Kusuma, Ajeng; Ainun Qolbi Wasdili, Fini; Mahargyani, Wikan (JURNAL KESEHATAN KARTIKA, 2024)
Background: Chronic renal failure is a condition of decreased kidney function, where the kidneys cannot function to remove metabolic waste in the body that accumulates in the blood. In the end stage of chronic renal failure, hemodialysis therapy is needed to remove the rest of the body's metabolism that accumulates in the blood and reduce the risk of death. The effectiveness of hemodialysis can be seen from the decrease in serum ureum levels in patients with chronic renal failure after hemodialysis therapy. Objective: to determine the description of serum ureum levels in pre and post hemodialysis chronic renal failure patients at X Hospital in 2022 and to get an overview of the effect of hemodialysis on ureum levels. Method: Descriptive Analytic with Cross sectional design. Data collection was done by using a questionnaire. Furthermore, the data were analyzed using the paired sample t-test statistical test. Results: The results obtained p value = 0.000 (α ≤ 0.05) means that there is a difference in ureum levels of chronic renal failure patients before and after undergoing hemodialysis. Conclusion: There was a decrease in serum ureum levels of chronic renal failure patients after hemodialysis therapy, but not all returned to normal values.